2009
DOI: 10.1093/schbul/sbn174
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Profile in Early-Onset Schizophrenia-Spectrum Disorders: Measured With the MATRICS Battery

Abstract: The MATRICS battery is sensitive in detecting differences between patients and controls in the adolescent population. However, we question the use of Mayer-Salovey-Caruso Emotional Intelligence Test in this age group. Results document a significant generalized deficit in adolescents with EOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 38 publications
7
74
1
3
Order By: Relevance
“…Despite this, we have controlled for IQ and SES differences through further analysis of covariance. As has been found in previous reports, our results showed that cognitive deficits are a relevant trait of EOS beyond patients' lower IQ and lower SES [32,38,57]. Regarding academic grade, our results confirmed previous reports which showed that EOS patients achieve worse educational level [3,61] and showed that such worse achievements were present from initial stages of the illness independently from IQ and SES.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Despite this, we have controlled for IQ and SES differences through further analysis of covariance. As has been found in previous reports, our results showed that cognitive deficits are a relevant trait of EOS beyond patients' lower IQ and lower SES [32,38,57]. Regarding academic grade, our results confirmed previous reports which showed that EOS patients achieve worse educational level [3,61] and showed that such worse achievements were present from initial stages of the illness independently from IQ and SES.…”
Section: Discussionsupporting
confidence: 91%
“…Although it may be a controversial issue, groups were not matched by IQ, academic grade or SES. As EOS is associated with compromised general cognitive intellectual ability [36] and schizophrenia is associated with low socioeconomic status, especially in patients with low cognitive abilities [60], matching the groups in these areas could actually remove the effect of the disease, leading to biased comparisons between overachieving patients and underachieving controls [20,38]. Despite this, we have controlled for IQ and SES differences through further analysis of covariance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall long term outcomes in area of social and vocational domains remain unfavourable [1]. Cognitive impairment precedes the emergence of positive and negative symptoms and appears to persist throughout the course of the disorder [2,3]. Expert consensus concludes that the negative outcomes are strongly related to the severity of impaired neuro-cognition (INC).…”
Section: Introductionmentioning
confidence: 99%